2017
DOI: 10.1021/acs.nanolett.7b03734
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Inspired Design of Nanoparticle Artificial Antigen-Presenting Cells for Immunomodulation

Abstract: Particles engineered to engage and interact with cell surface ligands and to modulate cells can be harnessed to explore basic biological questions as well as to devise cellular therapies. Biology has inspired the design of these particles, such as artificial antigen-presenting cells (aAPCs) for use in immunotherapy. While much has been learned about mimicking antigen presenting cell biology, as we decrease the size of aAPCs to the nanometer scale, we need to extend biomimetic design to include considerations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 64 publications
7
141
0
Order By: Relevance
“…While some work has been done to use nanoparticles as aAPCs, the majority of examples developed insofar are on the microscale due to their higher efficacy. Clear evidence for this has been demonstrated by Schneck and others . However, designing aAPCs is not trivial.…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 78%
“…While some work has been done to use nanoparticles as aAPCs, the majority of examples developed insofar are on the microscale due to their higher efficacy. Clear evidence for this has been demonstrated by Schneck and others . However, designing aAPCs is not trivial.…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 78%
“…This close proximity increases the probability that both receptors can simultaneously bind to their respective ligands on CTLs, resulting in increased cellular proliferation . Nanoparticle size also plays a similar role, as increases in diameter can tighten the gap between the two signals to promote enhanced interactions with TCRs by providing multivalent binding . However, because larger nanoparticles may exhibit decreased lymphatic drainage, it has been recently demonstrated that decoupling the two signals and including them on different nanoparticles can maximize T cell stimulation while still maintaining the advantages of nanoscale aAPCs .…”
Section: Biomimetic Anticancer Nanovaccinesmentioning
confidence: 99%
“…This point was further reinforced by a recent study that demonstrated that the sizes of nanoparticles used as substrate for artificial antigen presenting cells is critical in T cell activation. 22 Therefore, if nanoparticle or nanoparticle cluster is below certain threshold size, then even increased ligand density may not be sufficient to properly stimulate a T cell response. 22 …”
Section: Nanomedicine As Immune-modulating Agentsmentioning
confidence: 99%
“…22 Therefore, if nanoparticle or nanoparticle cluster is below certain threshold size, then even increased ligand density may not be sufficient to properly stimulate a T cell response. 22 …”
Section: Nanomedicine As Immune-modulating Agentsmentioning
confidence: 99%